Defining Gender-Responsive Services in a Juvenile Court Setting - Anderson, Valerie R. (Women & criminal justice, 2019)
Scholars have documented the importance of developing gender-responsive services for girls in order to address their unique needs and reasons for entering the juvenile justice system. Although researchers have made progress in efforts to develop gender-responsive services, the research and policy literature does not provide a clear definition of what constitutes a gender-responsive approach. This study examined qualitative interviews with juvenile court staff (N = 39). Court staff lacked familiarity with gender-responsivity and most used the term interchangeably with gender-specificity. However, multiple court staff expressed a need for programming for girls and more research on the effectiveness of gender-responsive services.